Microbiology and antibiotic sensitivity of uncomplicated chronic suppurative otitis media at Dr. George Mukhari Academic Hospital, South Africa - Kotu, Monica; Olwoch, Ian Paul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The study was conducted to assess the type and frequency of isolation of different microorganisms in uncomplicated chronic suppurative otitis media (CSOM) and their antibiotic sensitivity in our institution. Methods: A total of 88 consecutive patients with unilateral or bilateral active, chronic suppurative otitis media attending outpatient department at DGMAH were included in the study after obtaining an informed consent. There were 55 males (62.5%) and 33 females (37.9%) with age range between 6 months and 76 years. Pus swabs were taken through the perforation site and from the promontory after ear mopping under direct vision. Results: Children less than 5 years were more affected (23.9%) than older children 5-10 years (13.6%) and 11-15 years (11.45%). One hundred and six microorganisms were isolated from analysis of cultures obtained from 72 patients. Seven cultures were negative (5.9%), 8 specimens were contaminated (6.7%) and 1 specimen was lost (1.1%). Pseudomonas aeruginosa (24.0%) was the most common isolate, followed by Staphylococcus aureus (17%) and Proteus mirabilis (10%). Drug sensitivity pattern showed that Piperacillin-tazobactam was effective against the majority of Pseudomonas aeruginosa isolates at 72%, followed by both Gentamicin and Ceftazidime at 64% and Ciprofloxacin at 48%. Staphylococcus aureus isolates were sensitive to Erythromycin (77%), Cloxacillin and Clindamycin at 72%. Proteus mirabilis was sensitive to Cefuroxime (91%), Co-amoxiclav (72.8%). Conclusions: Isolation rate and susceptibility patterns in CSOM, suggest a need for regular surveillance to monitor antimicrobial resistance and to guide antibacterial therapy.